Bovine Papillomavirus 1 Gets Out of the Flock: Detection in an Ovine Wart in Sicily - Savini, Federica (Pathogens, 2020)
A proliferative cauliflower lesion was excised from the udder of a sheep. Histological investigation confirmed the macroscopic classification of the lesion as a papilloma, without any fibroblastic proliferation. PCR revealed the presence of bovine papillomavirus (BPV), which was further confirmed by the identification of a Deltapapillomavirus 4 by Next Generation Sequencing analysis. This was subsequently classified as bovine papillomavirus type 1. Negative staining electron microscopy (EM) analyses produced negative test results for papillomavirus particles. RNA in situ hybridization (ISH) confirmed the presence of BPV-1. The results further confirm the ability of BPVs belonging to the Deltapapillomavirus genus to infect distantly related species and to cause lesions that are different from sarcoids.